Jurisprudential Interpretation and Digital Worship: A Critical Study of the Muhammadiyah Fatwa on Virtual Friday Prayers - Ilyas, Hamim (Journal of Islamic Law, 2025)
The rapid development of digital technology has transformed not only patterns of social communication but also modes of religious practice, thereby challenging the framework of classical Islamic jurisprudence (fiqh). This article examines Muhammadiyah’s fatwa rejecting the validity of conducting Friday prayers in a virtual format during the COVID-19 pandemic, focusing on the interpretive model underpinning this legal determination. Employing a qualitative, text-based approach, the study treats the fatwa as an Islamic legal text, analyzing it in terms of its structure, argumentation, and sources of authority. Data were collected from official fatwa publications on the digital platform Suara Muhammadiyah and supplemented with relevant institutional documents. The findings reveal that Muhammadiyah employs a textual-normative interpretive model, grounded in tafsīr bi al-maʾthūr (tradition-based exegesis), which emphasizes strict adherence to the prophetic model in ritual worship (ʿibādah maḥḍah). The fatwa asserts that virtual congregations do not fulfill the physical and spatial requirements of communal prayer and that the legitimate alternative in emergencies is the performance of Ẓuhr prayer. These findings suggest that Muhammadiyah’s approach represents a careful negotiation between textual fidelity and technological adaptation, illustrating how modern fatwa-issuing institutions navigate doctrinal continuity in the face of challenges in the digital era. [Perkembangan pesat teknologi digital telah mengubah tidak hanya pola komunikasi sosial, tetapi juga praktik keagamaan, sehingga menantang kerangka fikih klasik. Artikel ini menganalisis fatwa Muhammadiyah yang menolak keabsahan pelaksanaan salat Jumat secara virtual selama pandemi COVID-19, dengan menyoroti model interpretatif yang melandasi penetapan hukum tersebut. Melalui pendekatan kualitatif berbasis teks, penelitian ini memperlakukan fatwa sebagai teks hukum Islam yang dianalisis dari segi struktur, argumentasi, dan landasan otoritasnya. Data diperoleh dari publikasi resmi fatwa pada platform digital Suara Muhammadiyah serta berbagai dokumen kelembagaan terkait. Hasil analisis menunjukkan bahwa Muhammadiyah menerapkan model interpretasi tekstual-normatif yang berakar pada tafsīr bi al-maʾthūr, dengan penekanan pada kepatuhan ketat terhadap model kenabian dalam ranah ibadah (ʿibādah maḥḍah). Fatwa tersebut menegaskan bahwa salat Jumat secara virtual tidak dapat memenuhi syarat fisik dan spasial salat berjamaah, dan bahwa alternatif yang sah dalam kondisi darurat adalah salat zuhur. Temuan ini memperlihatkan bahwa pendekatan Muhammadiyah merepresentasikan prinsip kehati-hatian dalam menegosiasikan antara kesetiaan terhadap teks dan adaptasi terhadap teknologi, sekaligus menggambarkan bagaimana lembaga fatwa modern menegosiasikan kesinambungan doktrinal dengan tantangan kontemporer di era digital.]